Mentalization-Based Group Therapy for Adolescents with Avoidant Personality Disorder: Adaptations and Findings from a Practice-Based Pilot Evaluation. (3rd July 2019) - Bo, Sune; Bateman, Anthony; Kongerslev, Mickey T.
ABSTRACT: Avoidant personality disorder (AVPD) is amongst the most severe personality disorders (PDs) and associated with a marked reduction in social functioning. However, AVPD research is sparse and little is known about treatment efficacy. In adolescents with AVPD even less is known about the disorder, and no studies have investigated the effect of psychotherapeutic treatment for this group. In this study, we present a new group-oriented treatment approach, Mentalization-Based Treatment for Avoidant Adolescents (MBT-AA), based on Mentalization-Based Treatment (MBT) principles and with elements from positive psychotherapy. Furthermore, we report on findings from a small MBT-AA case example and show that the treatment program reduces avoidant personality pathology, internalizing pathology and increases mentalization. We discuss the results and the potential empowering aspects of this new approach.